Prompt Oseltamivir Therapy Reduces Medical Care and Mortality for Patients With Influenza Infection. Issue 27 (July 2015) - Wang, Chang-Bi; Chiu, Mu-Lin; Lin, Po-Chang; Liang, Wen-Miin; Chen, Chiu-Ying; Chang, Yu-Jun; Wu, Trong-Neng; Wang, Jen-Hsien; Sung, Fung-Chang; Nagafuchi., Seiho
<x xml:space="preserve">Abstract</x> Abstract There are limited population-based studies on the progress of oseltamivir therapy for influenza infection. Using insurance claims data of 2005, 2009, and 2010, the authors established an "in-time" cohort and a "lag-time" cohort representing influenza patients taking the medicine within and not within 1 week to examine the treatment progress. Incident outpatient visit, emergency care and hospitalization, and fatality were compared between the 2 cohorts in the first week and the second week of follow-up periods, after the oseltamivir therapy. A total of 112, 492 subjects diagnosed with influenza on oseltamivir therapy in 2005, 2009, and 2010 were identified. The multivariate logistic regression analysis showed that the in-time treatment was superior to the lag-time treatment with less repeat outpatient visits, hospitalizations, and fatality. The overall corresponding in-time treatment to lag-time treatment odds ratios (OR) were 0.50, 0.54, and 0.71 (all P value < 0.05), respectively. The in-time to lag-time ORs of all events were 0.50 in 2009 and 0.54 in 2010. Our study demonstrates that the in-time oseltamivir therapy leads to significantly better treatment outcomes. Oseltamivir should be administered as early as the onset of influenza symptoms appears.